Safety of community drinking-water and outbreaks of waterborne enteric disease: Israel, 1976-97 - Tulchinsky Theodore H.; Burla Etti; Clayman Marla; Sadik Chantal; Brown Alex; Goldberger Shalom (The World Health Organization, 2000)
Waterborne disease remains a major public health problem in many countries. We report findings on nearly three decades of waterborne disease in Israel and the part these diseases play in the total national burden of enteric disease. During the 1970s and 1980s, Israel?s community water supplies were frequently of poor quality according to the microbiological standards at that time, and the country experienced many outbreaks of waterborne enteric disease. New regulations raised water quality standards and made chlorination of community water supplies mandatory, as well as imposing more stringent guidelines on maintaining water sources and distribution systems for both surface water and groundwater. This was followed by improved compliance and water quality, and a marked decline in the number of outbreaks of waterborne disease; no outbreaks were detected between 1992 and 1997. The incidence of waterborne salmonellosis, shigellosis, and typhoid declined markedly as proportions of the total burden of these diseases, but peaked during the time in which there were frequent outbreaks of waterborne disease (1980-85). Long-term trends in the total incidence of reported infectious enteric diseases from all sources, including typhoid, shigellosis, and viral hepatitis (all types) declined, while the total incidence of salmonellosis increased. Mandatory chlorination has had an important impact on improving water quality, in reducing outbreaks of waterborne disease in Israel, and reducing the total burden of enteric disease in the country.